The Reconfiguration of Trade Law in the Name of Sustainability, Responsibility, and Inclusion: Multilateral, Plurilateral, and National Dynamics in Tension - Dufour, Geneviève (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
This article examines the contemporary transformation of international trade law, which is tending to open to the objectives of sustainable development, human rights protection and inclusion. It explores how this transition towards sustainable, responsible and inclusive trade manifests itself through multilateral, plurilateral and national dynamics. By analyzing these three levels of governance, the article shows that trade law, far from being a simple tool for liberalization, has in recent years become a vector for normative change, bringing with it promises but also risks of fragmentation and exclusion.